2017
DOI: 10.1155/2017/7582398
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Parental and Friend Social Support and Children’s Physical Activity and Time Spent outside Playing

Abstract: The purpose of this study was to examine the structural validity of a parent and a child questionnaire that assessed parental and friends' influences on children's physical activity and investigate the associations between the derived factors, physical activity, and time spent outside. Children (N = 154, mean age = 11.7) and 144 of their parents completed questionnaires assessing parental and friends' influences on children's physical activity. Children wore a pedometer for six days. Exploratory factor analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…Additionally, two studies were identified from searches of reference lists, resulting in 25 articles. A posteriori, four studies [51,52,53,54] were excluded because they reported bivariate results only. Thus, finally 21 studies were included in this review, reporting data on 30 independent samples in total.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, two studies were identified from searches of reference lists, resulting in 25 articles. A posteriori, four studies [51,52,53,54] were excluded because they reported bivariate results only. Thus, finally 21 studies were included in this review, reporting data on 30 independent samples in total.…”
Section: Resultsmentioning
confidence: 99%
“…Co-participation in PA allows, not only direct parental role modelling, but also occasions for encouragement and support to develop motor skills and feelings of competence [ 20 ]. Several studies among school-aged children argue that frequent co-participation in PA increases children’s PA levels [ 22 , 23 ], although it is also stated that friends and other social environments may be more important to school-aged children’s PA than parents’ participation [ 24 , 25 ]. A greater role of parents may be expected among pre-school-aged children’s daily activity choices due to children’s early developmental stages [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pre-school-aged child that is involved in PA needs parental involvement in reaching the places for the activity, some form of parental support in engaging the activity, and parental presence throughout the activity. Previous studies state that co-participation in PA as a family seems to be greatest during early childhood [ 24 , 25 ]. However, to our knowledge, only one study has specifically studied the influence of co-participation in PA on pre-school children’s activity levels.…”
Section: Introductionmentioning
confidence: 99%
“…Validity against interviews for the child‐ and parent reported items were reported as an ICC of 0.24 with 51% agreement, and an ICC of 0.56 with 57% agreement, respectively. The factor analysis performed by Loucaides and colleagues identified one specific factor for ‘parental physical activity with child’ (i.e. co‐participation).…”
Section: Resultsmentioning
confidence: 99%